2005
DOI: 10.1101/lm.97505
|View full text |Cite
|
Sign up to set email alerts
|

Social recognition memory requires two stages of protein synthesis in mice

Abstract: Olfactory recognition memory was tested in adult male mice using a social discrimination task. The testing was conducted to begin to characterize the role of protein synthesis and the specific brain regions associated with activity in this task. Long-term olfactory recognition memory was blocked when the protein synthesis inhibitor anisomycin was injected 20 min before, immediately after, or 6 h after sampling. No effect was observed when anisomycin was administered 3 h or 18 h after sampling. Immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 31 publications
6
91
0
2
Order By: Relevance
“…Perhaps reflecting the importance of these brain regions for regulating maternal behaviour, such as recognition of pup vocalisations & scents (Cohen et al, 2015;Richter et al, 2005), gender differences in oxytocin receptor expression have been reported. For example, denser receptor expression was found in the piriform cortex in female compared to male mice .…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensory mentioning
confidence: 99%
“…Perhaps reflecting the importance of these brain regions for regulating maternal behaviour, such as recognition of pup vocalisations & scents (Cohen et al, 2015;Richter et al, 2005), gender differences in oxytocin receptor expression have been reported. For example, denser receptor expression was found in the piriform cortex in female compared to male mice .…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensory mentioning
confidence: 99%
“…Scale bar, 100 m. p Ͻ 0.03, ANOVA with Bonferroni correction for multiple comparisons). Piriform cortex is an olfactory area believed to be important for learned odor associations and several forms of social behavior (Haberly and Bower, 1989;Richter et al, 2005;Cohen et al, 2015). Second, hippocampal CA2 in females had more OXTR-2ϩ cells than in other regions of the hippocampal formation (Fig.…”
Section: Oxtr-2 a Novel And Specific Antibody To The Mouse Oxytocin mentioning
confidence: 99%
“…Brains were removed, postfixed in 4% formaldehyde diluted in PBS for 20 h and transferred to 1 M sucrose in PBS for another 20 h. The brains were shock frozen in isobutanol and stored at Ϫ80°C until cryosectioning. Floating frontal sections (40 m) were incubated with an antibody raised against a peptide mapping at the N terminus of human c-Fos p62 (identical to the corresponding mouse sequence; c-Fos sc-42; 1:20000; Santa Cruz Biotechnology) for 4 d. c-Fosimmunoreactive cells were visualized using a biotinylated goat antirabbit secondary antibody (1:2000, Jackson Laboratory) and the ABC method (Richter et al, 2005). The number of c-Fos-immunoreactive cells was determined using a Zeiss microscope (Axiophot) and a computer program (ImageJ; http://rsbweb.nih.gov/ij/).…”
Section: C-fos Immunohistochemistrymentioning
confidence: 99%